Corporate governance and cash dividend policy : evidence from Chinese IPOs / Nirosha Hewa Wellalage … [et al.] - Hewa Wellalage, Nirosha; Fouzi, Fitriya; Gaoxiang, Wang; Basyith, Abdul (Accounting Research Institute (ARI), Faculty of Accountancy & UiTM Press, 2014)
This paper investigates the relationship between corporate governance mechanisms and cash dividend payment in newly listed firms in China. Using 142 initial public offerings (IPO) listed on the Shenzhen Stock Exchange (SZSE), a dynamic panel Tobit regression is employed. The result shows that large, profitable IPOs with large boards and a high proportion of independent and female directors and CEO duality are willing to pay high dividends to their shareholders. This study indicates the requirement for the promulgation or streamlining of corporate laws in emerging markets to reduce the possibility of expropriation of minority shareholders by politically powered large shareholders.